MD Anderson manual of psychosocial oncology - Duffy, James D.; Valentine, Alan D. (New York McGraw-Hill Medical, 2011)
"During the past two decades, very significant advances have been made in our understanding and treatment of the psychosocial consequences of cancer. The standard of care in clinical oncology now includes recognition of the psychosocial consequences of cancer, treatment of psychiatric syndromes associated with the disease, and relief of bio-psycho-social-spiritual distress and suffering common to the cancer experience for patients and caregivers. Because the scope of the problem is great and the number of dedicated psycho-oncologists is few, comprehensive cancer care is not delivered by specialists alone. Primary oncologists of all disciplines and the growing interdisciplinary subspecialty of psycho-oncology has done much to help establish this standard of care and to develop a research and clinical framework to support it. Psychosocial oncology is not just another subspecialty. It represents a philosophy of care that seeks to bring together the interdisciplinary team working together to address the particular needs of a patient, family, and community. Implementing such a care delivery model in the culture of our current high technology hierarchical healthcare systems can be a real challenge. However, these barriers cannot be allowed to prevent the implementation of a person-centered model of care that has been demonstrated to improve patient outcomes, decrease costs, and enhance healthcare professional satisfaction. Oncology and psychosocial oncology should take a leadership role in developing and championing this model of healthcare"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cancer -- Psychological aspects -- Handbooks, manuals, etc; Cancer -- Social aspects -- Handbooks, manuals, etc; Neoplasms -- Psychology; Neoplasms -- Therapy